PENGEMBANGAN KAPASITAS TEKNOLOGI INFORMASI PEGAWAI KANWIL DJP JAKARTA SELATAN II MELALUI PELATIHAN MS. EXCEL TINGKAT DASAR - Noni Juliasari; Rusdah; Dewi Kusumaningsih; Ratna Ujiandari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2020)
Abstract The achievement of company goals can be achieved optimally when employees have adequate competence in understanding their roles and responsibilities. Therefore, the agenda for developing employee capacity is also an important mission in increasing employee competence, one of which is through training activities. Computer training for Directorate General of Taxation employees is intended so that the absorption of Information Technology can contribute to increasing productivity and the quality of employee performance. Based on the operational data processing needs of their current jobs, the training was focused on using Microsoft Office programs, especially Microsoft Excel. It is hoped that through the Microsoft Office training program, especially the basic level of Microsoft Excel, for employees of the Directorate General of Taxes, Regional Office II, South Jakarta, can be a useful contribution to increasing the ability of employees so that their productivity and quality of performance increase. Abstrak Pencapaian tujuan perusahaan mampu dicapai secara optimal manakala para pegawai memiliki kompetensi yang memadai dalam memahami peran dan tanggungjawabnya. Oleh sebab itu, agenda pengembangan kapasitas pegawai juga merupakan misi penting dalam meningkatkan kompetensi pegawai salah satunya dengan kegiatan pelatihan. Pelatihan komputer bagi para pegawai Direktorat Jendral Pajak dimaksudkan agar penyerapan Teknologi Informasi dapat menjadi kontribusi peningkatan produktivitas dan kualitas kinerja para pegawai. Berdasarkan kebutuhan pengolahan data operasional pekerjaan mereka saat ini, maka pelatihan dipusatkan pada penggunaan program Microsoft Office terutama Microsoft Excel. Diharapkan melalui program pelatihan Microsoft Office terutama Microsoft Excel tingkat dasar bagi para pegawai Direktorat Jendral Pajak Kanwil II Jakarta Selatan dapat menjadi kontribusi yang bermanfaat untuk peningkatan kemampuan para pegawai agar produktifitas dan kualitan kinerja mereka meningkat.